The increased risk for autoimmune diseases in patients with eating disorders. - Anu Raevuori; Jari Haukka; Outi Vaarala; Jaana M Suvisaari; Mika Gissler; Marjut Grainger; Milla S Linna; Jaana T Suokas (PLoS ONE)
Objective Research suggests autoimmune processes to be involved in psychiatric disorders. We aimed to address the prevalence and incidence of autoimmune diseases in a large Finnish patient cohort with anorexia nervosa, bulimia nervosa, and binge eating disorder. Methods Patients (N = 2342) treated at the Eating Disorder Unit of Helsinki University Central Hospital between 1995 and 2010 were compared with general population controls (N = 9368) matched for age, sex, and place of residence. Data of 30 autoimmune diseases from the Hospital Discharge Register from 1969 to 2010 were analyzed using conditional and Poisson regression models. Results Of patients, 8.9% vs. 5.4% of control individuals had been diagnosed with one or more autoimmune disease (OR 1.7, 95% CI 1.5-2.0, P<0.001). The increase in endocrinological diseases (OR 2.4, 95% CI 1.8-3.2, P<0.001) was explained by type 1 diabetes, whereas Crohn's disease contributed most to the risk of gastroenterological diseases (OR 1.8, 95% CI 1.4-2.5, P<0.001). Higher prevalence of autoimmune diseases among patients with eating disorders was not exclusively due to endocrinological and gastroenterological diseases; when the two categories were excluded, the increase in prevalence was seen in the patients both before the onset of the eating disorder treatment (OR 1.5, 95% CI 1.1-2.1, P = 0.02) and at the end of the follow-up (OR 1.4, 95% CI 1.1-1.8, P = 0.01). Conclusions We observed an association between eating disorders and several autoimmune diseases with different genetic backgrounds. Our findings support the link between immune-mediated mechanisms and development of eating disorders. Future studies are needed to further explore the risk of autoimmune diseases and immunological mechanisms in individuals with eating disorders and their family members.